Case Report: Long-term follow-up of multiple giant coronary artery aneurysm associated with multisystem inflammatory syndrome in children - Arici, Sule; Genc, Fatih Alparslan; Yagar Keskin, Gulperi; Corbacioglu, Serafettin; Surekli Karakus, Ozlem; Yildirim, Ayse Inci; Sungur, Metin; Tas, Erkan (Frontiers in Pediatrics, 2025)
IntroductionMultisystem inflammatory syndrome in children (MIS-C) is a rare but serious condition that emerged during the COVID-19 pandemic. While most coronary artery abnormalities in MIS-C are transient, the potential for persistent or progressive coronary aneurysms remains unclear. This report presents the long-term follow-up of a pediatric MIS-C case with multiple giant coronary artery aneurysms.Case presentationA 4-year-old boy presented with 13 days of persistent fever during the COVID-19 pandemic. MIS-C was diagnosed based on high-grade fever, markedly elevated inflammatory markers, recent SARS-CoV-2 exposure, and coronary artery involvement on echocardiography. The patient showed rapid clinical improvement following treatment with intravenous immunoglobulin, corticosteroids, aspirin, and enoxaparin. Cardiac catheterization at 8 weeks confirmed multiple giant aneurysms in the right and left coronary arteries. He remained asymptomatic and was followed with echocardiography and ECG every 3 months. After 30 months, repeat catheter angiography revealed persistent giant aneurysms, though with slightly reduced dimensions.ConclusionThis case highlights that multiple giant coronary artery aneurysms associated with MIS-C may persist even after long-term follow-up, despite clinical and laboratory improvement. It underscores the need for extended cardiac monitoring and prolonged antithrombotic therapy in children with severe coronary involvement.